Effect of acibenzolar S-methyl on vascular wilt (Fusarium oxysporum f. sp. niveum) of watermelon - RAMÍREZ BUSTOS, IRENE ILIANA; FERNÁNDEZ HERRERA, ERNESTO; SALDARRIAGA NOREÑA, HUGO; ORTEGA ROSAS, CARMEN ISELA; LÓPEZ PÉREZ, MARI CARMEN (Ecosistemas y Recursos Agropecuarios, 2025)
Vascular wilt caused by Fusarium oxysporum f. sp. niveum (Fon) is the main fungal disease of watermelon crops. Acibenzolar-S-methyl (ASM) is an inducer of plant defenses, which is effective against diseases caused by viruses, bacteria and fungi. In the present study, the effect of ASM on mycelial growth, spore germination and the reduction of the severity of wilting caused by Fon1, as well as its toxicity in watermelon plants was evaluated. The inoculation of the fungus was carried out four days after the application, via irrigation and foliar, of the ASM at concentrations of 15, 20, 30 and 40 mg L-1 in seedlings with two true leaves of the Sugar Baby variety, which does not have Fon resistance genes. In vitro results showed that ASM has a direct effect on spore germination and mycelial growth of Fon1. Also, the application of the defense inducer in watermelon plants significantly reduced (P < 0.05) the severity of wilt caused by Fusarium. The application via irrigation of the defense inducer (15 mg L-1) was more effective than the foliar application, since it reduced the severity of wilting caused by Fon1 in watermelon plants by 100%. The doses of 30 and 40 mg L-1 caused toxicity symptoms, since the plants showed significantly lower height, number of leaves and fresh aerial weight, compared to non-inoculated and untreated plants.
Keywords: Fon1; ASM; Fusarium wilt; severity; toxicity